1983
DOI: 10.1002/aic.690290302
|View full text |Cite
|
Sign up to set email alerts
|

Pressure drop for cocurrent downflow of gas‐solids suspensions

Abstract: 13-mm insidediameter tube was investigated using 329-micron spherical glass beads in air. The gas Reynolds number varied from 0 to 30,oOO with solids-loading ratios of up to 20 at a gas Reynolds number of l0,oOO. The frictional pressure drop for downflow was found to be a weaker function of the solids-loading ratio than the upflow case using data reported in the literature. Empirical correlation of the t w q h a s e friction factor, in terms of the gas Reynolds number and a dimensionless parameter, C D E~D / [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Limited early studies were reported by Shimizu et al (1978) and Kim and Seader (1983). Limited early studies were reported by Shimizu et al (1978) and Kim and Seader (1983).…”
Section: Brief Historymentioning
confidence: 99%
“…Limited early studies were reported by Shimizu et al (1978) and Kim and Seader (1983). Limited early studies were reported by Shimizu et al (1978) and Kim and Seader (1983).…”
Section: Brief Historymentioning
confidence: 99%
“…The axial behaviors in downer reactors have been investigated for long [8][9][10][11][12][13][14]. During these experiments, the superficial gas velocity (SGV) remains unchanged along the reactor length.…”
Section: Introductionmentioning
confidence: 99%
“…However, our understanding of gas-solids two-phase flow in the CDCFB, especially in units near to pilot scale, is still limited. Kim and Seader investigated a CDCFB with a 13 mm ID tube and spherical glass beads of 329 ym [2]. Wang et al studied the hydrodynamics of a CDCFB with a 140 mm ID tube and…”
Section: Introductionmentioning
confidence: 99%